Misdiagnosis of Herlyn–Werner–Wunderlich syndrome combined with pelvic mesothelial cyst: a case report - Li, Jinrong; Duan, Qiong; Long, Na; Ji, Fengming; Hang, Yu; Yang, Zhen; Xie, Yucheng; Zhanghuang, Chenghao; Yan, Bing (Frontiers in Medicine, 2025)
Herlyn–Werner–Wunderlich syndrome (HWWS) combined with pelvic mesothelial cyst is a rare condition that can be easily misdiagnosed. Our center presents a case study of this disease to provide clinicians with valuable insights for accurate diagnosis and treatment. A 12-year-old girl initially received a misdiagnosis of left lower abdominal ectopic kidney hydronephrosis based on B-ultrasound and renography due to intermittent abdominal pain. However, surgical exploration revealed the correct diagnosis of HWWS with pelvic mesothelial cyst. Postoperative pathology confirmed the presence of a mesothelial cyst in the pelvis. Once the diagnosis was confirmed, the patient was transferred to an adult gynaecology department for further treatment. Two months later, during follow-up via telephone, it was reported that the patient had successfully recovered after undergoing transvaginal oblique septum resection. This case report provides detailed information on the diagnostic process, treatment procedures, and examination results, serving as a valuable reference for clinical practitioners dealing with HWWS combined with pelvic mesothelial cysts while reducing the risk of misdiagnosis and mistreatment.